2011
DOI: 10.1103/physreva.84.053617
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of heat capacity of an attractive Bose-Einstein condensate approaching collapse

Abstract: We report the calculation of heat capacity of an attractive Bose-Einstein condensate, with the number N of bosons increasing and eventually approaching the critical number N cr for collapse, using the correlated potential harmonics (CPH) method. Boson pairs interact via the realistic van der Waals potential. It is found that the transition temperature T c initially increases slowly, then rapidly as N becomes closer to N cr . The peak value of heat capacity for a fixed N increases slowly with N , for N far away… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…(69). There has been a lively discussion of the influence of the shape and dimensionality of the confining potential on the existence, form and evolution of this feature [6,31,33,35,36,[40][41][42][43]. As our results show, the sharpness of the resonance can be effectively controlled by the voltage applied to the attractive Robin surface.…”
Section: Bosonsmentioning
confidence: 63%
See 1 more Smart Citation
“…(69). There has been a lively discussion of the influence of the shape and dimensionality of the confining potential on the existence, form and evolution of this feature [6,31,33,35,36,[40][41][42][43]. As our results show, the sharpness of the resonance can be effectively controlled by the voltage applied to the attractive Robin surface.…”
Section: Bosonsmentioning
confidence: 63%
“…10(a) demonstrate. The cusp-like structure of the heat capacity that was predicted theoretically for a number of the confining potentials [35,36,[40][41][42][43] and observed experimentally for, e.g., the dilute Bose gas of 87 Rb atoms [44], for the infinite number of particles, N = ∞, turns at T = T cr into the discontinuity that is a manifestation of the phase transition; in our case, it is a transition from the BE condensate to the normal phase of the noninteracting particles in the linear potential. This justifies the definition of the critical temperature from Eq.…”
Section: Bosonsmentioning
confidence: 99%
“…Another method to arrive at it is to zero the denominator in Equation (56) what results in infinite specific heat at the transition point. This highly asymmetric cusp-like shape of the specific heat was intensively analyzed theoretically [4,5,65,67,69,70,[91][92][93][94] and demonstrated experimentally. At the infinite number of bosons, N = ∞, the cusp-like shape at T = T cr becomes a discontinuity disclosing in this way a phase transition; namely, in this particular situation, it is a transition from the BE condensate to the normal phase of the noninteracting corpuscles in the asymmetric Robin QW.…”
Section: Bosonsmentioning
confidence: 94%
“…At the infinite number of bosons, N = ∞, the cusp-like shape at T = T cr becomes a discontinuity disclosing in this way a phase transition; namely, in this particular situation, it is a transition from the BE condensate to the normal phase of the noninteracting corpuscles in the asymmetric Robin QW. This highly asymmetric cusp-like shape of the specific heat was intensively analyzed theoretically [4,5,64,66,68,69,[90][91][92][93] and demonstrated experimentally [94]. For the single Robin wall with the negative extrapolation length, it was shown that the sharpness of this feature can be effectively controlled by the applied voltage [4].…”
Section: Bosonsmentioning
confidence: 94%
“…Note that throughout this study the density n is kept fixed, thus T 0 serves below as a scaling unit in all temperature and energy-related dependencies. In contrast, the effect of finite number of particles and the trap curvature in the weakly-intaracting Bose gas above the transition temperature can be found, e.g., in [16,17].…”
Section: Formalismmentioning
confidence: 95%